2009
DOI: 10.1007/s11368-009-0125-6
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of anthropic pressures on soil phosphorus availability, concentration, and phosphorus forms in sediments in a Southern Brazilian watershed

Abstract: Purpose The transfer of soil sediments and phosphorus from terrestrial to aquatic systems is a common process in agricultural lands. The aims of this paper are to quantify the soil phosphorus availability and to characterize phosphorus forms in soil sediments as contaminant agents of waters as a function of anthropic pressures. Materials and methods On three subwatersheds with different anthropic pressure, water and sediment samples were collected automatically in upstream and downstream discharge points in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 23 publications
0
9
0
2
Order By: Relevance
“…A long-term study in two important river basins in the state of Rio Grande do Sul showed that soluble P levels in freshwater are two-fold higher than the eutrophication limit, and that these high P concentrations are due to nonpoint sources of pollution from agriculture (Diel et al, 2007;Marchezan et al, 2009;Pellegrini et al, 2010). The fact that farmers in Southern Brazil are gradually using broadcast surface P application, in order to reduce time spent on planting, increases the potential for runoff losses.…”
Section: Introductionmentioning
confidence: 99%
“…A long-term study in two important river basins in the state of Rio Grande do Sul showed that soluble P levels in freshwater are two-fold higher than the eutrophication limit, and that these high P concentrations are due to nonpoint sources of pollution from agriculture (Diel et al, 2007;Marchezan et al, 2009;Pellegrini et al, 2010). The fact that farmers in Southern Brazil are gradually using broadcast surface P application, in order to reduce time spent on planting, increases the potential for runoff losses.…”
Section: Introductionmentioning
confidence: 99%
“…O P, por estar associado à fração sólida, as fontes não protegidas têm maior probabilidade de receberem material externo e apresentarem valores altos de P na água. Contudo, as fontes que compõem o subgrupo C apresentou PT elevado, o que sugere que grande parte do P presente nessas amostras se encontre em estado solúvel, como observaram PELLEGRINI et al (2010 (1) *Significância entre proteção (1 x 2) pelo teste t, a 5%, comparando as médias M1 dos subgrupos (A1vsA2; B1vsB2 e C1vsC2), em que n = 8; (2) * Significância entre locais (A x B x C) pelo teste t, a 5%, comparando as médias M2 dos grupos (AvsB; AvsC e BvsC), em que n = 16; ns é não significativo; A cor é expressa pela Unidade de Hazen (uH) e definida pela Portaria 518/2004(BRASIL, 2004.…”
Section: Resultsunclassified
“…Moreover, as there was no correlation between SSC and the proportions of cropland and/or forest, it was evident that other factors play an important role in sediment yield, such as distribution of croplands and forests in the landscape. Indeed, the shape of the landscape strongly influences sediment concentration in the catchment, and preserved riparian vegetation can serve as a barrier, decreasing the amount of sediments transferred to the water bodies (Pellegrini et al, 2010). Even when almost all crop fields of the catchment were plowed to transplant tobacco, the values of SSC in all six sampling sites in the three sub-basins and in the catchment outlet were lower than those observed during the storm event that occurred in the fallow period (Table 2).…”
Section: Effect Of Land Use and Soil Management On Suspended Sedimentmentioning
confidence: 99%
“…These fields are in steeply sloped areas, resulting in a large amount of sediment (Pellegrini et al, 2010;Bonumá et al, 2012;Bonumá et al, 2014;Tiecher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%